Records of the Inquisition as a Historical Source: Th eir Potential, Limitations, and Strategies of Reading - Zbíral, David (Dějiny – teorie – kritika, 2012)
In his article, the author focuses on the current state of research in records of the Inquisition with the aim to evaluate the limitations and kinds of bias characteristic of this type of sources. Th is includes not only the most frequently cited types of bias stemming from the very set-up of the situation (inquisitor’s questionnaire, his power over the written record, his terminology, educational background, etc.) but also the strategies of self-presentation and identity construction of the part of the person under interrogation. The author justifies his support for a detailed individual study of various inquisitional registers – indeed even of different depositions – which should replace the rather common notion of inferring their reliability from general ideas about the inquisitional procedure. He identifies three main ‘strategies of reading’ ( J. H. Arnold) of such sources which should help facilitate the extraction of useful data from inquisitional records, namely, the mapping of a space of agency which an individual deponent had, the mapping of different ‘surpluses’ (C. Bruschi) or ‘excesses of speech’ ( J. H. Arnold) in the inquisitional records, and finally, a narrative analysis of the depositions, inspired by the theoretical framework of narratology and narrative psychology. The author emphasises that the question of reliability of inquisition records goes beyond source criticism. Indeed, it has complex relations to some of the very central discussions in epistemology of historical and social sciences, in particular to discussions about the relationship between reality and representation connected with the ‘linguistic turn’. Regarding this point, the author argues that in the system of relations between the historian, the inquisitor, and the deponent, none of the parties involved should automatically be seen as authentic. Narrative psychologists have shown that there is no such thing as an ‘authentic’ or ‘real’ identity. Instead, identity is always created within a particular discursive situation. Any search for an ‘authentic voice’ therefore necessarily leads to a dead end. That also implies that there is no given or necessary difference in reliability of trial records and literary texts about one’s self or between ‘direct’ and ‘indirect’ sources. Any source, inquisitional or not, is biased by a certain policy of representation and identity construction.